2012
DOI: 10.1186/1471-2172-13-41
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional role of dextran sulfate sodium for in vivo modeling of intestinal diseases

Abstract: BackgroundInflammatory bowel diseases (IBDs) are chronic, relapsing disorders that affect the gastrointestinal tract of millions of people and continue to increase in incidence each year. While several factors have been associated with development of IBDs, the exact etiology is unknown. Research using animal models of IBDs is beginning to provide insights into how the different factors contribute to disease development. Oral administration of dextran sulfate sodium (DSS) to mice induces a reproducible experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 51 publications
3
27
0
Order By: Relevance
“…Neovascularisation is a key pathological feature of human IBD [29], however DSS-associated neovascularisation was previously shown to be associated with repair and re-epithelialisation [30]. Consistent with this, we showed an increase in CD31 + staining in DSS challenged KO mice (Figure 1f), consistent with reduced histopathological scoring in this group.…”
Section: Resultssupporting
confidence: 88%
“…Neovascularisation is a key pathological feature of human IBD [29], however DSS-associated neovascularisation was previously shown to be associated with repair and re-epithelialisation [30]. Consistent with this, we showed an increase in CD31 + staining in DSS challenged KO mice (Figure 1f), consistent with reduced histopathological scoring in this group.…”
Section: Resultssupporting
confidence: 88%
“…These tissue changes were milder in mice treated with 1% DSS ( Figure 1C). Thus, we demonstrated that higher concentrations of DSS induced more severe and irreversible intestinal injury, which is consistent with a previous study (20). Thus, we asked whether the severity of disease related to pro-inflammatory cytokines, including IL-6, and TNF-α, which are directly involved in the pathogenesis of UC (4,5).…”
Section: Resultssupporting
confidence: 89%
“…The mice were allowed to recover by removing DSS from their drinking water, yielding a period that bears resemblance to the remission period in IBD patients [33]. Analysis of clinical symptoms revealed that WT mice showed significantly faster decrease in faecal blood indices (figure 4a) and watery stool consistency (figure 4b) compared with ZnR/GPR39 KO mice, although both genotypes continued to lose weight even following the removal of DSS (figure 4c).…”
Section: (C) Recovery Phase: Following Dss Removalmentioning
confidence: 99%